Nueva Clínica Stella Maris. Del barrio al claustro en un proyecto hospitalario - Quequezana Vidalon, Melanie Margarita (2023)
The COVID-19 pandemic put on the front page the national importance of being prepared for emergencies, disasters and various social crises. The ability to provide quality health services without interruptions becomes indispensable, and the design of hospital architecture is a way of addressing the multiple factors that transform society, health, and the urban environment. With the Mother House of the Missionary Mothers of the Sacred Heart remaining as the only vestige of the original design, the extension of the Stella Maris Clinic, designed by the architect Paul Linder in 1948, becomes a precise case study for the identification and analysis of strategies for the design of an optimal hospital program, which have been lost today. Faced with this situation, a proposal is designed that reinterprets the architectural qualities designed by Linder, in order to recover the architectural quality of health services, while promoting integration and positive impacts on the nearby urban environment. The investigation starts from the analysis of the original planimetry of the PUCP Architecture Archive, to identify strategies and potential elements for the project. These are superimposed on the data collected “in situ”, where current project changes are identified, for the preparation of graphs that support the proposal. The value of the convent on which the design of the old clinic was born is recognized and respected, in addition to the architectural and urban contributions of the proposal designed by the architect Linder, in order to design a proposal that meets the needs of the current program , recovering the interior free spaces essential for quality in health services, in addition to promoting the connection between the New Stella Maris Clinic and its urban environment.